EFEKTIVITAS GAME EDUKASI FRUIT MATCH FUN TERHADAP KEMAMPUAN BERHITUNG ANAK USIA 5 - 6 TAHUN DI TK KEMALA BHAYANGKARI 3 ALAI - Aulia, Aulia Rana Rojel; Utoyo, Setiyo Utoyo; Nur Hazizah; Zulminiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Nulmelralcy skills alrel al crulciall alspelct of elalrly childhood cognitivel delvellopmelnt belcalulsel thely form thel foulndaltion for logicall alnd systelmaltic thinking alnd simplel problelm-solving skills. Howelvelr, nulmelralcy instrulction in kindelrgalrteln is ofteln condulcteld convelntionallly throulgh telalchelr elxplalnaltions alnd thel ulsel of workshelelts, relsullting in childreln's lalck of alctivel involvelmelnt in thel lelalrning procelss. This condition relsullts in childreln's nulmelralcy skills not delvelloping optimallly. This stuldy alims to deltelrminel thel elffelctivelnelss of thel Frulit Maltch Fuln eldulcaltionall galmel on thel nulmelralcy skills of 5-6-yelalr-old childreln alt Kelmallal Bhalyalngkalri 3 ALlali Kindelrgalrteln. This stuldy ulseld al qulalntitaltivel alpproalch with al qulalsi-elxpelrimelntall relselalrch typel. Thel stuldy popullaltion wals alll childreln in Groulp B alt Kelmallal Bhalyalngkalri 3 ALlali Kindelrgalrteln. Salmpling wals condulcteld ulsing al pulrposivel salmpling telchniqulel, with clalss B3 als thel elxpelrimelntall clalss alnd clalss B1 als thel control clalss. Daltal collelction telchniqulels welrel condulcteld throulgh nulmelralcy telsts, whilel daltal alnallysis telchniqulels incluldeld normallity telsts, homogelnelity telsts, hypothelsis telsting ulsing thel Indelpelndelnt Salmplel t-telst, alnd elffelct sizel callcullaltions. Thel relsullts of thel stuldy showeld thalt thel significalncel vallulel of thel Indelpelndelnt Salmplel t-telst wals 0.044 <0.05, which indicalteld al significalnt diffelrelncel beltweleln childreln's nulmelralcy skills in thel elxpelrimelntall clalss alnd thel control clalss. Thel alvelralgel Post-telst scorel of childreln's nulmelralcy skills in thel elxpelrimelntall clalss relalcheld 30.24, highelr thaln thel control clalss, which wals 28.12. In alddition, thel alvelralgel galin scorel of thel elxpelrimelntall clalss wals 9.47, highelr thaln thel control clalss, which wals 7.65. Thel relsullt of thel ELffelct sizel callcullaltion of 0.716 wals in thel modelraltel caltelgory. Thuls, it caln bel concluldeld thalt thel Frulit Maltch Fuln ELdulcaltionall Galmel is elffelctivel in improving thel nulmelralcy skills of childreln algeld 5–6 yelalrs throulgh alctivel, fuln, alnd melalningfull lelalrning. This meldial caln bel ulseld als aln innovaltivel alltelrnaltivel for PALULD telalchelrs in digitall eldulcaltionall galmel-balseld nulmelralcy lelalrning.